Pregnancy Related Acute Renal Failure: An Experience at a Tertiary Care Hospital - Syeda Haleema Abdullah, Asma Aziz, Shumaila Kanwal, Shermeen Kousar, Sadia Ahmad, Naureen Ghani (Pakistan Journal of Medical & Health Sciences, 2023)
The aim of this study to evaluate the magnitude of PRAF (Pregnancy related acute renal failure) in Pakistan, contributing factors responsible for pregnancy related acute kidney failure, the results of treatment options for ARF in pregnancy, including cure rates, maternal mortality, and other factors. Study design: It was a cross sectional study, conducted at the department of Obstetrics and Gynaecology, Fouji Foundation Hospital, Rawalpindi and Jinnah Teaching Hospital, Peshawar from January, 2023 to June, 2023. Methodology: A total number of participant was (N=250). The age of participants was 20-37 years included pregnant women. Serum electrolytes complete blood count, renal function test and urine routine were performed on all participants. Results: The median age was 27.05±4.8 years. Most of the participant’s residency were belong to the rural areas 72% and most cases was occurred during third trimester 42%. The participants was included 60% conservative treatment and 40% hemodialysis. When compared both groups’ pre-treatment and post-treatment in dialysis, urine production and all biochemical indicators were exhibited significant (P <0.001) improvement. The urea, creatinine, Na, K and urine output were significantly higher in dialysis group than conservative group, p<0.0001. Maternal outcomes was improved 98.6% in conservative group, and 70% improved in dialysis group. Conclusion: In conclusion, renal failure and maternal difficulties interact intricately to cause PRARF. To get the greatest results, the management strategy whether conservative or incorporating dialysis—should be customized to the unique clinical circumstances of each patient. Improving maternal and newborn health outcomes and reducing the hazards connected with PRARF. Keywords: Chronic, Acute, Kidney and Dialysis.